Modeling of cooking strip loin and outside round steaks in a forced-air convection oven - Obuz, E.; Erickson, Larry E.; Hunt, Melvin C.; Herald, T.J.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used a forced-air convection oven to cook steaks from two muscles; strip loin (longissimus lumborum) and outside round (biceps femoris). We used a mathematical model to predict cooking time and temperature profiles for each steak. No differences (P>0.05) were found in cooking times between experimental and model values for either of the steaks. Modeled temperature profiles were consistently higher (except for the beginning of the cooking cycle) than the experimental values up to 65°C (150°F) in the cooking cycle for outside round steaks, whereas better agreement between experimental and modeled values was found for strip loin steaks. A highly positive linear relationship was found between experimental and modeled temperature histories for both strip loin (R2=0.99) and outside round (R2=0.96) steaks. The developed model should be useful for steak cooking, because the constant time to a given degree of doneness should increase consumer satisfaction by reducing variation in degree of steak doneness.
Keywords: Beef; Strip loin; Outside round steaks; Forced-air convection oven